A Novel Biostimulant–Biochar Strategy for Improving Soil Quality and Salinity Tolerance in Medicinal Mint (Mentha longifolia L.) - Mamdouh A. Eissa; Modhi O. Alotaibi; Mashael M. Alotibi; Alya Aljuaid; Taghreed Hamad Aldayel; Adel M. Ghoneim (Soil Systems, 2025)
This study evaluated the combined application of biochar (BC) and Spirulina platensis (SP) as a sustainable strategy to improve soil quality and salinity tolerance in mint (Mentha longifolia L.) cultivated in sandy soils. A pot experiment was conducted using saline irrigation water (5 dS m−1) with four treatments: control, BC alone, SP alone, and BC + SP applied at 1% (w/w), arranged in a randomized complete block design with three replicates. Salt stress reduced plant height and biomass yield by 16% and 27%, respectively, and increased sodium (Na+) in shoots by 74%, causing ionic imbalance and decreased soil microbial biomass carbon by 19%. The combined BC + SP treatment significantly improved soil microbial biomass carbon (SMBC) by 100%, reduced soil Na⁺ by 41%, and enhanced K+/Na+ and Ca2+/Na+ ratios by 138% and 133%, respectively. Under salinity, BC + SP increased nutrient concentrations in mint shoots, including N (120%), P (106%), K (88%), Ca (67%), Fe (70%), Mn (50%), Zn (44%), and Cu (70%), and improved leaf chlorophyll content. These results demonstrate that BC and SP synergistically mitigate salinity stress by improving soil properties, nutrient uptake, and ionic balance, making BC + SP a promising sustainable amendment for saline sandy soils.